RUANG KEBEBASAN BERTHEOLOGI PEREMPUAN ACEH DALAM WILAYATUL HISBAH DI NANGGROE ACEH DARUSSALAM (NAD) - Ridwan Hasan (Media Syari'ah, 2017)
Nanggroe Aceh Darussalam (NAD) is a region that has implemented a system in accordance with Islamic Shari’a Qanun. 11 in 2002, and has also been stipulated in Law no. 44, 1999. In Regional Regulation no. 5 years of 2000 and no. 33 year of 2001that is better known in the community called Qanun Aceh. Account that there are various items in the Qanun, which gives the freedom to form to be actions feminism in both attitudes, thoughts or theology form to Allah are still in the corridor to be take shelter from Wilayatul Hisbah by the color of the Islamic Law. The scope of freedom for women is a must according to age in the era globalizations a very necessary contribution in the context of a change in thinking that the women in order to obtain various forms of freedom that is still in the provisions set out in the Qanun, which as far as the rules of sharia marginal of rule to feminism at Islam in a different color.